Understanding organizational behavior - Moorhead, Gregory; Griffin, Ricky W. (Andover, Mass. : Cengage Learning Asia Pte Ltd, 2013)
This edition takes on that charge by providing the basics in each area, bolstered by the latest research in the field, and infused with examples of what companies are doing in each area.
Foundations of organizational behavior -- Organizations and individuals -- Groups in organizations -- Processes in organizations
Includes bibliographical references.
Keywords: ORGANIZATIONAL BEHAVIOR